2014
DOI: 10.5704/moj.1411.005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice of Diabetic Foot Care in an In- Patient Setting at a Tertiary Medical Center

Abstract: Good knowledge and practice regarding diabetic foot care will reduce the risk of diabetic foot complications and ultimately amputation. This study is conducted to assess patients' knowledge and compliance of diabetic foot care.A cross sectional study performed on patients who were admitted to HSNZ from the 1st September 2013 to 30th April 2014 for diabetic foot infections. They were interviewed with a questionnaire of 15 'yes' or 'no' questions on foot care knowledge and practice. Score of 1 was given for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
70
7
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(121 citation statements)
references
References 8 publications
11
70
7
6
Order By: Relevance
“…There was no significant difference between males and females for this indicator. This finding was comparable with other related studies, which also reported the same pattern of scoring for knowledge and practice of foot care [16,17]. Many other studies showed the presence of inadequate knowledge of self-foot-care in diabetic patients [18,19].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…There was no significant difference between males and females for this indicator. This finding was comparable with other related studies, which also reported the same pattern of scoring for knowledge and practice of foot care [16,17]. Many other studies showed the presence of inadequate knowledge of self-foot-care in diabetic patients [18,19].…”
Section: Discussionsupporting
confidence: 81%
“…This result seems to be in contrast with the available literature on foot care, where there is either no gender difference between both sexes [16] or males are usually reluctant to acknowledge their health problems and seek professional care [25,26].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Thirdly, these patients have been to a healthcare facility where it is generally presumed that education about foot care will be communicated to them before discharge. Some authors have cited the busy clinic duty schedule of the doctors as part of the reasons for this poor communication [8]. In our hospital it may be worse, as the patient to doctor ratio is quite high, which may leave the doctor with little time to spend with each patient.…”
Section: Discussionmentioning
confidence: 97%
“…DAE'lerin; iş gücü kaybına, sakatlıklara ve hastayı umutsuzluğa sürükleyen psikososyal travmalara da yol açabilmesi, buzdağının görünmeyen kısmıdır (9). Önceki yıllarda anaerob bakteriler ve Gram pozitif koklarla DAE sıklığı daha yaygın iken, artık pek çok ilaca dirençli Gram negatif bakterilerle oluşan enfeksiyonlar klinisyeni zorlamakta, etkin bir şekilde tedavi edilemeyen DAE'ler sonrası ayak ampütasyonu riski artmaktadır (2,10,11 Önceki ampütasyon varlığı (n) 1…”
Section: Introductionunclassified